Physical culture and recreation: a systematic review - Tetiana Yermakova (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. In recent years, there has been a growing interest in physical culture and recreation due to their significant impact on population health and quality of life. This work aims to systematically review research in the field of physical culture and recreation to identify current trends, issues, and prospects.